International Monetary System : Developments and Prospects. (IMF Working Papers; Working Paper ;, 1988)
This paper addresses several fundamental issues raised by recent developments in the world economy and considers their implications for the design and functioning of the international monetary system. We do not make any proposals. The four issues examined in the paper are: (1) Can the exchange rate regime do much to discipline fiscal policy?; (2) What are the extent and costs of reduced monetary independence under greater fixity of exchange rates?; (3) How can the equilibrium exchange rate best be determined?; and (4) Does a well functioning international monetary system require a clearly defined set of rules, an acknowledged leader, and an explicit anchor?.